How education from children influences parents' green travel behavior? The mediating role of environmental protection commitment - Zhang, Tong; Chen, Feiyu; Gu, Xiao; Li, Zhuohang; Zhu, Zhexin (Frontiers in Psychology, 2025)
The transmission of green ideas within families is no longer limited to the older generations instilling ideas into the younger generations. Younger generations are increasingly influencing the green travel behavior of older generations with their green ideas. This study was based on social learning theory and reverse socialization theory and proposed the concept of “trans-education.” A theoretical model of green travel factors was constructed based on self-efficacy and environmental protection commitment (EPC) and its dimensions. By conducting a field experiment (N = 229) and administering a questionnaire survey across 31 provinces in China (N = 639), it has been found that: (1) Trans-education significantly contributes to residents' green travel behavior. This finding means transmitting green concepts from the younger to the older generation can positively influence green travel behavior. (2) Trans-education influences residents' green travel behavior through EPC and its dimensions. (3) Self-efficacy reduces the extent to which trans-education affects residents' green travel behavior. These findings offer new perspectives on the relationship between intergenerational transmission of green concepts within families and green travel behavior changes.